2022
DOI: 10.1155/2022/5161703
|View full text |Cite
|
Sign up to set email alerts
|

Effect Evaluation of Dexmedetomidine Intravenous Anesthesia on Postoperative Agitation in Patients with Craniocerebral Injury by Magnetic Resonance Imaging Based on Sparse Reconstruction Algorithm

Abstract: The effect of dexmedetomidine on postoperative agitation of patients with craniocerebral injury was investigated based on magnetic resonance imaging (MRI) with the sparse reconstruction algorithm. Sixty patients with craniocerebral injury who underwent tracheal intubation and craniotomy hematoma removal under general anesthesia in hospital were selected as the research objects. Patients were randomly and averagely divided into the normal saline group (group A) and the dexmedetomidine (DEX) group (group B). DEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…The Riker Sedation-Agitation Scale was proposed by Riker in 1999 and is mainly used to assess the level of agitation during the recovery phase in patients undergoing treatment under general anesthesia. It has higher reliability and authenticity in evaluating the awakening status of mechanically ventilated patients compared to the widely used Ramsay Sedation Scale[ 16 , 17 ]. The present study’s findings indicate that the time to eye opening and extubation was significantly shorter in the observation group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The Riker Sedation-Agitation Scale was proposed by Riker in 1999 and is mainly used to assess the level of agitation during the recovery phase in patients undergoing treatment under general anesthesia. It has higher reliability and authenticity in evaluating the awakening status of mechanically ventilated patients compared to the widely used Ramsay Sedation Scale[ 16 , 17 ]. The present study’s findings indicate that the time to eye opening and extubation was significantly shorter in the observation group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that dexmedetomidine contributes to stabilizing blood circulation, safeguarding brain function, maintaining intracranial pressure stability, reducing cerebral oxygen metabolism, and providing analgesia and sedation. This renders it suitable for anesthesia during craniocerebral surgery [8][9][10]. Nevertheless, the precise mechanism underlying dexmedetomidine's brain-protective effects in patients undergoing craniocerebral surgery remains unclear, and there is insufficient evidence supporting its application in brain protection during such procedures.…”
Section: Introductionmentioning
confidence: 99%